PENGARUH RASIO KEUANGAN TERHADAP KEBIJAKAN DIVIDEN DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI - Anastassia, Cindy; Setijaningsih, Herlin Tundjung (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to determine the effect of activity, liquidity and solvency on dividend policy with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Dividend policy is still an issue because dilemma between interested parties have different goals. The purpose of investors is to get returns, while companies want to continue to develop their business so that there are companies that distribute dividend on a small scale or not at all. This research will use a causal associative design. Samples were taken based on purposive sampling method of 43 companies, so the data for this research amounted to 129. Processing of data using the method of moderated regression analysis with Eviews 12. The results of this research indicate that activities have negative and significant effect on dividend policy, liquidity and solvency has no significant and positive effect on dividend policy, firm size is able to moderate the effect of activity on dividend policy, firm size in unable to moderate the effect of liquidity and solvency on dividend policy.